PENGARUH LITERASI KEUANGAN, PERILAKU KEUANGAN DAN PENDAPATAN TERHADAP PENGELOLAAN KEUANGAN - Sulastri, Sulastri; Yusnita, Irni; Sari, Ayunda Ramlita (Ensiklopedia of Journal, 2025)
This research aims to determine the analysis of the influence of financial literacy, financial behavior and income on the financial management of Pariaman City village officials in 2024. The type of research used is descriptive quantitative research. The type and source of data used is primary data collected and processed by the researcher himself from the object. The population in this study were village officials throughout Pariaman City and the sample for this study was 55 Village Secretaries throughout Pariaman City. The sampling technique uses non-probability sampling with purposive sampling type. This research was conducted by distributing questionnaires to 55 Village Secretary respondents in Pariaman City. The data analysis techniques used in this research are descriptive statistical analysis, data quality test, classical assumption test, multiple linear regression test, t test, f test and coefficient of determination with the help of the SPSS Version 25 software program. The results of this study show that financial literacy is not has a significant effect on financial management, while financial behavior and income have a positive and significant effect on financial management. Keyword:Financial Literacy, Financial Behavior, Income, Financial Management